If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 1 = 2 + -1x Reorder the terms: 1 + 7x = 2 + -1x Solving 1 + 7x = 2 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 1 + 7x + x = 2 + -1x + x Combine like terms: 7x + x = 8x 1 + 8x = 2 + -1x + x Combine like terms: -1x + x = 0 1 + 8x = 2 + 0 1 + 8x = 2 Add '-1' to each side of the equation. 1 + -1 + 8x = 2 + -1 Combine like terms: 1 + -1 = 0 0 + 8x = 2 + -1 8x = 2 + -1 Combine like terms: 2 + -1 = 1 8x = 1 Divide each side by '8'. x = 0.125 Simplifying x = 0.125
| 2m-m+4m=15 | | 350=140r | | (6x^2+19x+2)+(-4x^2+10x-11)= | | -7+13b+(-6b)-b= | | y-2=7/3(x-6) | | 30+41= | | -5(1-5x)+5(-8x-2)=-4+-8x | | F(x)=5x^2+11x-12 | | -14k--19k-8k=-18 | | 4x^2-14x=2(2x^2-7x) | | 12x+5=17x-10 | | (x^2-4x+4)(x^2+9)= | | y-x^2= | | 4.5x-2=2.5x+8 | | s/19=150 | | 8b^5+20b^3+48H^4x^2=0 | | 14xd=154 | | 14k-19k-8k=18 | | 2(x-5)=4-7(7-x) | | -10-14b-3-(-5b)= | | 4a^2b^7+2ab^4-6ab^7= | | 8y-6x+7x= | | 7x-2(-10+5x)=11 | | 4+4y=95 | | 5x-11/3=43 | | -7(1-2m+n)= | | 2(x+5)=4-2(7+x) | | 2x+(x-5)=55 | | 15x^2y-35xy-20x= | | (9x-7)(5x+9)=0 | | 6y^2-10y+3=0 | | 17-(6x+3)= |